Pengaruh Komitmen Organisasi Dan Keterlibatan Kerja Terhadap Turnover Intention: Studi Pada Fasilitator SLRT Dinas Sosial Kabupaten Kolaka - Nur Hesty Ramadhani; Niar Astaginy; Hendrik Hendrik (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2023)
This study aims to determine: (1) The Effect Of Organizational Commitment on Turnover Intention (Study on the SLRT Facilitator of the Kolaka Regency Social Service). (2) The Effect Of Work Involvement on Turnover Intention (Study on the SLRT Faciliotator of the Kolaka Regency Social Service). This research uses a quantitative method approach. Data collection in this study used observation, documentation, and questionnaires. The population of this study were all facilitators who warked in Kolaka District Social Services. While the sample for this research consisted of 133 facilitators, the sample was determined using census techniques. Testing of research instruments using validity tests and relibility tests with SPSS 22.0. The data analysiS technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 4.0. Based on the research results, it is known that the Organizational Commitment variable has no effect on Turnover Intention as indicated by a P-Value of 0.104. And the Work Involvement variable has a positive and significant effect on Turnover Intention as indicated by a p-value of 0.035.